2x-4x-4x+x-9x=

Simple and best practice solution for 2x-4x-4x+x-9x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-4x-4x+x-9x= equation:


Simplifying
2x + -4x + -4x + x + -9x = 0

Combine like terms: 2x + -4x = -2x
-2x + -4x + x + -9x = 0

Combine like terms: -2x + -4x = -6x
-6x + x + -9x = 0

Combine like terms: -6x + x = -5x
-5x + -9x = 0

Combine like terms: -5x + -9x = -14x
-14x = 0

Solving
-14x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '-14'.
x = 0

Simplifying
x = 0

See similar equations:

| 4x+28=36 | | 2b^2-16b-40=0 | | k^2-4k-45=0 | | 2x+5(2+3x)=3x+2(14+12x)+8 | | -18-22=10x | | 14x=63-7x | | (x)2=200+(x-200)4 | | 4h-h=35+25 | | 7x-12y=4 | | -11x=3x-28 | | -2a^2+54a= | | (5+2x)*(3x-5)=0 | | -2a^2+54=0 | | 6x^3-17x^2+5x= | | -2a(a+27)=0 | | 4a^3+9a^2-4+2a^3-9a+9= | | 2x-8(7-x)=18 | | 22m+23=24m-25 | | x+-0.05x+1=n | | x+-0.05x+1= | | 7x+1=3(6x-7) | | 2s+6=s+13 | | 10x^2-6=7x | | x+-0.05x+1=1+11.95x | | (5-3x)(2+4x)= | | 6m+4=5m-1 | | -2[8-5(2-3x)-7x]=4(x+9) | | x+-0.05x+11.95x=1-1 | | X=(2x^2+3x-6)+(x^2-18x+6) | | 4x^2+3x-6=0 | | 6x^2-6x+10=2x^2-2x+25 | | x-0.5(0.1x-2)=1+11.95x |

Equations solver categories